Nineteenth Century Psychical Research in Mainstream Journals: The Revue Philosophique de la France et de l’Étranger - Alvarado, Carlos S.; Evrard, Renaud (Journal of Scientific Exploration, 2014)
<span style="font-family: "Times New Roman","serif"; font-size: 14pt; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">While there were several psychical research journals during the nineteenth century many interesting discussions about psychic phenomena took place as well in a variety of intellectual reviews and scholarly and scientific journals of various disciplines. One such example was the French journal Revue Philosophique de la France et de l’Étranger founded in 1876 by Théodule Ribot. Reflecting the various interests of psychologists during the nineteenth century many topics were discussed in the Revue, among them hypnotic phenomena, as well as mental suggestion and mediumship. The journal provided an important forum for French discussions in psychology and in the social sciences in general that helped the development of those disciplines. The same may be said about psychic phenomena, which were discussed in the pages of the Revue by authors such as Émile Boirac, Victor Egger, Théodore Flournoy, Jules Héricourt, Pierre Janet, Léon Marillier, Julian Ochorowicz, Charles Richet, and Albert Ruault. We present summaries of some of these writings which we hope will bring some of this material to the attention of non-French readers.